Intragastric injection of botulinum toxin A for weight loss: A systematic review and meta‐analysis of randomized controlled trials. Issue 6 (22nd April 2022) - Yen, Yi‐An; Wang, Chi‐Chih; Sung, Wen‐Wei; Fang, Kuan‐Chieh; Huang, Shih‐Ming; Lin, Chun‐Che; Tsai, Ming‐Chang; Yang, Tzu‐Wei
Abstract: Background and Aim: Intragastric botulinum toxin A (BTA) injection is a potential treatment for weight reduction in obese patients. Current studies yielded conflicting results. We performed a systematic review and meta‐analysis of randomized controlled trials (RCTs) to assess the efficacy of intragastric BTA injection for weight management. Methods: We searched several databases to identify RCTs evaluating intragastric BTA injections for obesity. We applied random‐effects models for all meta‐analyses due to heterogeneity in the included studies. The mean difference (MD) and 95% confidence interval (CI) were calculated for continuous outcomes. Results: A total of 6 RCTs including 192 subjects met the inclusion criteria and were included for the meta‐analysis. Although the pooled data from six studies showed no difference in the absolute weight loss between intragastric BTA injection and control, subgroup analysis showed a significantly decreased absolute weight after a BTA injection dose ≥ 200 U (MD, −2.04 kg; 95% CI, −3.96 to −0.12) and after multiple injection regions in the stomach combined with diet control (MD, −4.44 kg; 95% CI, −6.54 to −2.33 kg) compared with the control. Regarding absolute weight loss, the impact of endoscopic ultrasound‐guided injection and follow‐up duration showed no difference. Intragastric BTA injection had a significant change in body mass index (MD, −1.25 kg/m 2 ; 95% CI, −2.18 to −0.32 kg/m 2 ) and prolonged gastric half‐emptying time (MD, 11.37 min; 95% CI, −3.69 to 19.06 min). Conclusion: Intragastric BTA injection is effective for obesity treatment, and adequate doses (≥ 200 U), multiple gastric injection regions, and combined diet control are crucial. However, given the small sample size and limited power, caution should be exercised.